Microphotochemistry: 4,4'-Dimethoxybenzophenone mediated photodecarboxylation reactions involving phthalimides - Shvydkiv, Oksana; Nolan, Kieran; Oelgemöller, Michael (Beilstein Journal of Organic Chemistry, 2011)
A series of 4,4'-dimethoxybenzophenone mediated intra- and intermolecular photodecarboxylation reactions involving phthalimides have been examined under microflow conditions. Conversion rates, isolated yields and chemoselectivities were compared to analogous reactions in a batch photoreactor. In all cases investigated, the microreactions gave superior results thus proving the superiority of microphotochemistry over conventional technologies.
Keywords: microflow; microreactor; photochemistry; photodecarboxylation; phthalimide